Is my stress right or wrong? Studying the production of stress by non-native speaking teachers of English - Ika Apriani Fata (Universitas Syiah Kuala, 2014)
This study aims at exploring the production of stress by non native English teachers in Aceh. It also inquires into how these teachers of English overcame their shortcomings in oral English language teaching. 45 non native English teachers from Aceh were recorded. They came from four regions in the province of Aceh, namely Aceh Timur, Langsa, Aceh Utara and Aceh Besar. The participants have taught English from five to 15 years. The approach used in this paper is qualitative by focusing on the method of lexical stress analysis suggested by Crystal (1969), Halliday (1970) and McCawley (1986). The study reveals that variations of lexical stresses were produced by the teachers with 13-15 years of teaching experience. Those from Langsa and Aceh Timur produced the most varied stresses. Therefore, it is suggested for future research to conduct a more in-depth study on this topic with a wider sample of participants and more target words. It is also proposed that possible socio-phonological language inferences in the production of English stress by EFL teachers should be explored.